157k views
3 votes
The expression (x^3 )(x^(-17) ) is equivalent to (x^n). What is the value of n?

User LzyPanda
by
5.4k points

2 Answers

1 vote

Answer:

21

Explanation:

User Thomas Luzat
by
5.6k points
1 vote

Answer:


n=-14

Explanation:

The given expression is


(x^3)(x^(-17))=x^n

Recall that;
a^m* a^n=a^(m+n)

We apply this property to the left hand side to obtain;


x^(3+-17)=x^n

This simplifies to;


x^(3-17)=x^n


x^(-14)=x^n

Since the bases are the same; the exponents are also the same.


\therefore n=-14

User Sanchez
by
5.4k points